An Observational Study to Evaluate Infection Risk in Two Staff Warming Devices and a Review of Current Literature into Thermal Comfort in the Operating Room and Beyond - Mark Silverberg (Research and Practice in Anesthesiology, 2019)
Objective To compare the degree of bacteria dissemination using two currently available operating room (OR) personnel warming devices. The “off-label” use of 3MTM’s Bair HuggerTM vs. a fairly new device, worn around the torso and under a scrub warm-up jacket or surgical gown, the OPERATIONHEATJAC® transformer only (TRO) powered by a transformer and controlled by a 4-level controller, and best for anesthesia providers and perfusionists. Methods Initially, staff members in scrubs sat in a room for 3 and 6-hours with agar plates placed in various positions throughout the room. Then staff members sat in the same room under the same conditions for 3 and 6-hours, and placed the hose from 3M’s Bair Hugger under their scrubs. Agar plates were positioned in the room in the same positions as in the control. Then staff members sat in the same room under the same conditions for 3 and 6-hours, wearing the OPERATIONHEATJAC® TRO over their scrub shirt and under a scrub warm-up jacket. Agar plates were again positioned in the room in the same positions as in the control. Bacteria colony counts were compared. Results The bacteria colony counts were 43.78% and 46.18% higher at 3 and 6-hours respectively from placement of the hose from 3MTM’s Bair HuggerTM under scrubs vs. the control. There was no significant difference in bacteria colony counts with using the OPERATIONHEATJAC® TRO vs. the control. Conclusion ORs are maintained cold, mostly for surgeon comfort. In an attempt to keep comfortable in this environment, peripheral OR staff opt for the “off-label” use of 3M’s Bair Hugger hose placed under scrubs. An increased spread of bacteria throughout the OR can result from this practice. Currently, there are now safer OR personnel warming devices available. In addition, this paper reviews the significance and benefits of keeping staff warm and comfortable.